Testing long-run neutrality of money in Malaysia - Muzafar Shah Habibullah,; Puah , Chin Hong; Azali Mohamed, (Penerbit Universiti Kebangsaan Malaysia, 2001)
Monetary aggregates movements and their influence on domestic economy are important and essential to policy makers and researchers. To the policy makers, the influence and the existence of special relationship between monetary aggregates and other macroeconomic variables are important in designing policies such as to curb inflation pressure, stimulating economic growth and reduce unemployment problem. On the other hand, the researchers may use these aggregates and their relations with macroeconomic variables to estimate a complex macro model of an economy. In Malaysia, traditionally, monetary aggregate has been the major monetary policy strategy. Targeting M1, M2 and M3 has been the main policy targets until the mid- I 990s. However, by the mid-1990s, the Central Bank of Malaysia (BNM) has shifted their policy strategy from monetary targeting to interest rate targeting. As a matter of fact, the de-emphasizing of monetary aggregates as intermediate target begins with the de-emphasizing of MI in 1987. One of the major reasons for de-emphasizing monetary aggregates as policy variables is the availability of alternative interest-bearing financial assets in the markets as a result of active financial liberalization in recent years. As a result of the shifting of money into interest- bearing financial assets, the relationship between money and income becomes unstable, consequently, monetary policy actions using monetary aggregates as targets become ineffective. Our question is: Does the move made by BNM to de-emphasis monetary aggregates point to the fact that money does not affect output in Malaysia? In other words, one can ask: Does changes in money bring about in the changes on real economic variables? If none of the real economic variables would change in response to the change in money, we say that money is neutral. The neutrality of money has important implications for the role of monetary policy. In monetary-business-cycle (MBC) models.